SUPERVISI AKADEMIK DI SMA NEGERI 1 LAMBITU - JUWAIDIN, JUWAIDIN (PPs UNJ, 2016)
This research is aimed at analizing: (1) The academic supervision, (2) The intensity of the academic supervision, (3) Evaluation of academic supervision, (4) Follow-up of academic supervision At SMA Negeri 1 Lambitu. This research took place in SMA Negeri 1 Lambitu Bima used a qualitative approach with a phenomenological method. The data were collected through; (1) in-depth interviews, (2) observation, (3) documentation study. Data analysis was performed in three ways: data reduction, data presentation, and verification. Then check the validity of data through triangulation of sources, methods and theories. The results showed the changes competence of the teaching profession after the academic supervision, as seen in changing patterns of teaching in the classroom, learning preparation tools, teachers become more motivated to develop their potential, increasing teachers' confidence and be able to do professional duties better.